2011
DOI: 10.1111/j.1600-6143.2011.03645.x
|View full text |Cite
|
Sign up to set email alerts
|

Skin Cancer in Transplant Recipients, Out of the Woods. Scientific Retreat of the ITSCC and SCOPE

Abstract: The International Transplant Skin Cancer Collaborative (ITSCC) is an organization of more than 300 members dedicated to the study and care of skin changes that develop in solid-organ transplant recipients. This group of medical and surgical dermatologists, transplant surgeons and basic science researchers was formed to better understand the basic science of transplant dermatology, and to work collaboratively to address the clinical challenges in this patient population. Transplant patients have an ~100-fold in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 33 publications
0
6
2
Order By: Relevance
“…The level and choice of drugs used as immunosuppressants in SOTR are well described as possible RF for skin cancer development . In contrast, we could not observe that the cumulative doses of azathioprine, cyclosporine, MMF or corticosteroids during the first year post‐transplantation associate with SCC development in analyses adjusted for age and gender.…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…The level and choice of drugs used as immunosuppressants in SOTR are well described as possible RF for skin cancer development . In contrast, we could not observe that the cumulative doses of azathioprine, cyclosporine, MMF or corticosteroids during the first year post‐transplantation associate with SCC development in analyses adjusted for age and gender.…”
Section: Discussioncontrasting
confidence: 84%
“…17,38,39 The level and choice of drugs used as immunosuppressants in SOTR are well described as possible RF for skin cancer development. 16,[40][41][42] In contrast, we could not observe that the cumulative doses of azathioprine, cyclosporine, MMF or corticosteroids during the first year post-transplantation associate with SCC development in analyses adjusted for age and gender. The fact that all patients were exposed to cyclosporine and prednisone during the first year post-transplantation may have limited detection of dose level differences in these immunosuppressants as potential RF for SCC formation.…”
Section: Discussioncontrasting
confidence: 71%
“…Among SOT recipients, the most frequently used immunosuppressive agents for the prevention of allograft rejection include azathioprine, mycophenolate mofetil, cyclosporine, tacrolimus, sirolimus, and prednisone. The immunosuppressive regimen the patient receives is of utmost importance as certain agents, especially azathioprine and cyclosporine, are associated with an increased risk of NMSC . Additionally, the higher the degree of immunosuppression the higher the risk of developing NMSC as shown by cardiothoracic transplant having the highest risk of SCC, with kidney recipients second, and liver recipients third .…”
Section: Discussionmentioning
confidence: 99%
“…11 It has been demonstrated that transplant recipients who developed skin cancer were exposed to higher doses of cyclosporine, azathioprine, prednisone, and mycophenolate mofetil. 12 Currently, of the immunosuppressive medications, only mammalian target of rapamycin (mTOR) inhibitors are known to have simultaneous immunosuppressive and antitumor properties. 11 There are reports of reduced incidence of cancer in organ transplant recipients who receive mTOR inhibitor therapy, which strongly indicates separate pathways for pharmacologic immunosuppression and oncogenesis.…”
Section: Discussionmentioning
confidence: 99%